2013
DOI: 10.4161/psb.25477
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dopamine on root growth and enzyme activity in soybean seedlings

Abstract: In the present study, we investigated the effects of dopamine, an allelochemical exuded from the velvetbean (Mucuna pruriens L DC. var utilis), on the growth and cell viability of soybean (Glycine max L. Merrill) roots. We analyzed the effects of dopamine on superoxide dismutase, phenylalanine ammonia-lyase and cell wall-bound peroxidase activities as well as its effects on lignin contents in the roots. Three-day-old seedlings were cultivated in half-strength Hoagland nutrient solution (pH 6.0), without or wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 32 publications
0
16
0
6
Order By: Relevance
“…Therefore, this could be the mode of action by which dopamine inhibits root growth, as was observed in the growth of soybean seedling roots. 31 Carbohydrate levels changed in plants that transformed with dopamine synthesis genes showed that dopamine are linked with sugar metabolism. 23 In previous study, overexpression of TYDC in potatoes increased the content of glucose and sucrose.…”
Section: Plant Growth and Developmentmentioning
confidence: 99%
“…Therefore, this could be the mode of action by which dopamine inhibits root growth, as was observed in the growth of soybean seedling roots. 31 Carbohydrate levels changed in plants that transformed with dopamine synthesis genes showed that dopamine are linked with sugar metabolism. 23 In previous study, overexpression of TYDC in potatoes increased the content of glucose and sucrose.…”
Section: Plant Growth and Developmentmentioning
confidence: 99%
“…1,9,11,12,18,19 Some research has shown that the toxicity of dopamine, in both animal and plant cells, is related to the synthesis of melanin and it is ROS dependent. 20,21 Overall, ROS can attack cellular components, denaturing and inhibiting proteins, causing damage to DNA and membranes, blocking the absorption of nutrients and preventing root growth. 13 By evaluating seed germination by different plant species on a filter paper in the presence of the L-DOPA, precursor of dopamine, Nishihara et al 22 observed a correspondence between alterations in the color of the paper and reduction of root.…”
Section: Discussionmentioning
confidence: 99%
“…Yamato et al 20 using X-band electron spin resonance (ESR), provided evidence for ROS generation during dopamine metabolism in neurons. In addition, Guidotti et al 21 suggested that the increase in SOD activity and the decrease in cell viability in soybean root could be associated to augmented contents of ROS as a consequence of dopamine-induced oxidative stress, due its transformation into melanin.…”
Section: Discussionmentioning
confidence: 99%
“…Esses metabólicos liberados no meio podem afetar a germinação, o crescimento, a fisiologia e até mesmo os aspectos genéticos de plantas adjacentes (HARUN et al, 2014). Nos processos fisiológicos e bioquímicos os aleloquímicos podem interferir na utilização da água, na expansão foliar, na fotossíntese, no metabolismo dos aminoácidos e síntese protéica, na glicólise, na respiração mitocondrial e na síntese de ATP, entre outros (GUIDOTTI et al, 2013). A estimativa desse potencial pode ser realizada através de testes com espécies vegetais bioindicadoras, que são mais sensíveis à ação de metabólitos e que têm sido amplamente utilizadas em atividades laboratoriais, com baixo custo e alta eficiência, dentre as quais está a alface (KLEIN et al, 2014;ZORTÉA et al, 2015;MASUM et al, 2016).…”
Section: Ação Alelopática De Folhas Secas De Umbu Em Processo De Decunclassified